Adsorptive removal kinetics of anionic dye onto chitosan films doped with graphene oxide: An in situ fluorescence monitoring - Kahya, Nilay; Kaygusuz, Hakan; Akın Evingür, Gülşen; Erim, F. Bedia; BENER, SEMİRA (Taylor & Francis Inc, 530 Walnut Street, Ste 850, Philadelphia, Pa 19106 USA, 2018)
The aqueous adsorption of a fluorescent dye (pyranine) onto crosslinked chitosan-graphene oxide composite films was studied. In situ fluorescence monitoring technique is introduced as easy and fast experimental technique to select optimal adsorbent conditions. The effect of ionic crosslinker on adsorption was studied with sodium tripolyphosphate, trisodium citrate, and sodium sulfate, respectively. Among the crosslinkers, it was realized that sodium sulfate crosslinked films showed a greater adsorption rate for pyranine than the other two types of crosslinked films. Recently, graphene oxide is of interest as a filler compound for many biopolymer applications due to its favorable thermal, mechanical and surficial properties. In the present study, graphene oxide incorporation increased adsorption rate of the dye and the mechanical strength of ionically crosslinked chitosan films. The adsorption behavior of the adsorbent was explained by a kinetic model. Samples were characterized using scanning electron microscopy, thermogravimetric analysis, swelling experiments and tensile testing method.
Keywords: Adsorption; chitosan; crosslinker; graphene oxide; pyranine; Alginate Beads; Effective Adsorbent; Aqueous-Solution; Composite; Efficient; Water